The Uses of Media Literacy - Potter, John and Mcdougall, Julian and Bennett, Pete (Taylor & Francis, 2020)
Revisiting Richard Hoggart’s classic work The Uses of Literacy (1957), this book applies Hoggart’s framework to media literacy today, examining media literacy’s various uses, the tensions between them and what this means for people, communities and the contemporary configurations of social class. In The Uses of Literacy (1957), Richard Hoggart wrote about how his working class community, in the North of England, were at once using the new ‘mass literacy’ for self-improvement, education, social mobility and civic engagement and, at the same time, the powerful were seizing the opportunity also to use this expansion in literacy, through the new popular culture, for commercial and political ends. Working in the intersection between education, cultural studies and literacies, the authors write about media literacy as a contested, under-theorised field through Hoggart’s ‘line of sight’ to provide a perspective on media literacy and working class culture today. This reimagining of a classic work, piercingly relevant to studies of class in Britain in 2019, will be of key interest to scholars in Media Studies, as well as interested readers in Communication Studies, Literacy Studies, Cultural Studies, Politics and Sociology.
https://katalog.adlr.link/Record/51-9781032400341